The effectiveness of PNF method in rehabilitation of patients after ischemic stroke - Marlena Zakrzewska; Joanna Iłżecka (Kazimierz Wielki University, 2018)
Introduction. Stroke is a major medical and social problem. One of the methods used in neurodevelopmental rehabilitation of patients after ischemic stroke is the method of Proprioceptive Neuromuscular Facilitation (PNF). Objective of the work. Evaluation of effectiveness of PNF method in rehabilitation of patients after ischemic stroke. Material and methods. The study included 100 patients with ischemic stroke. In the study group (A) an individual rehabilitation program included the rehabilitation of the classical method and PNF, in the control group (B) of the patients were only streamlines the traditional individual rehabilitation. Degree of disability was evaluated on the basis of the modified Rankin scale, the level of movement disorders examined scale Brunnström. To assess the functional status of the patients was used functional indicator "Repty" and modified the RMA. Results. After the rehabilitation method of PNF, an improvement in mobility upper and lower limb in more than 60% of patients was observed. The degree of disability decreased in 40% of patients. There has been improvement in overall motor performance of 25.57% and greater independence in performing activities of daily living of 15.94%. Conclusions. Rehabilitation method of PNF is effective in patients after ischemic stroke; however, this method is not more efficient than conventional physiotherapy. Traditional physiotherapy cannot be excluded from effective methods of rehabilitation of patients after ischemic stroke.